Comparing the Self- and External Assessment Versions of the HCL-33 as Screening Instruments for Bipolar Disorder in Older Depressed Patients - Zhang, Xinqiao; Li, Wen; Zhao, Na; Jin, Yu; Cheung, Teris; Ungvari, Gabor S.; Cui, Xi-Ling; Wang, Gang; Xiang, Yu-Tao; Angst, Jules (Frontiers in Psychiatry, 2021)
Objectives: The misdiagnosis of bipolar disorder (BD) as major depressive disorder (MDD) is common in depressed older adults. The self-rated HCL-33 and its external assessment version (HCL-33-EA) have been developed to screen for hypomanic symptoms. This study compared the screening ability of these two instruments to discriminate BD from MDD. Method: A total of 215 patients (107 with BD and 108 with MDD) and their carers were recruited. Patients and their carers completed the HCL-33 and HCL-33-EA, respectively. The consistency of the total score and the positive response to each item between the two scales was calculated with the intraclass correlation coefficient (ICC) and Cohen’s kappa coefficient separately. Receiver operating characteristics (ROC) curves were drawn for both instruments. The optimal cut-off points were determined according to the maximum Youden’s Index. The area under the ROC curve (AUC) of the HCL-33 and HCL-33-EA were calculated separately and compared. The sensitivity and specificity at the optimal cut-off values were also calculated separately for the HCL-33 and HCL-33-EA. Results: The intraclass correlation coefficient (ICC) between the total scores of the HCL-33 and HCL-33-EA was 0.823 (95%CI=0.755-0.862). The positive response rate on all items showed high agreement between the two instruments. ROC curve analysis demonstrated that the total scores of both HCL-33 and HCL-33-EA differentiated well between MDD and BD (P<0.001), while there was no significant difference in the AUCs between the two scales (0.901 vs. 0.909, P=0.673). The optimal cutoff values for the HCL-33 and HCL-33-EA were 14 and 12, respectively. With the optimal cutoff value, the sensitivity and specificity of the HCL-33 and HCL-33-EA were 88.80% and 93.50%, and 82.40% and 79.60%, respectively. Conclusion: Both the HCL-33 and HCL-33-EA had good screening ability for discriminating BD from MDD in depressed older adults.